The Problem of Evil in the L. Petrushevskaya’s Novel “Number One, or in the Gardens Other Facilities” (Филологический класс, 2013)
In this article the analysis of L. Petrushevskaya’s “horror novel” is undertaken. Its moral and philosophical problems and the function of the literary conventionality in the reconstruction of modern Boschiad are detected. It is shown how the harsh writing manner, mystical fantasy as well as the method of metempsychosis serve to comprehension of the mechanism of “infection” and “poisoning” with evil; the intertextual dialogue with Dostoyevsky indoctrinates to the awaken-ing of conscience and cleansing of souls.